TGF‐β‐activated kinase‐1 inhibitor LL‐Z1640‐2 reduces joint inflammation and bone destruction in mouse models of rheumatoid arthritis by inhibiting NLRP3 inflammasome, TACE, TNF‐α and RANKL expression. Issue 1 (19th January 2022) - Tenshin, Hirofumi; Teramachi, Jumpei; Ashtar, Mohannad; Hiasa, Masahiro; Inoue, Yusuke; Oda, Asuka; Tanimoto, Kotaro; Shimizu, So; Higa, Yoshiki; Harada, Takeshi; Oura, Masahiro; Sogabe, Kimiko; et al.
Abstract: Objectives: Aberrant NLRP3 inflammasome activation has been demonstrated in rheumatoid arthritis (RA), which may contribute to debilitating inflammation and bone destruction. Here, we explored the efficacy of the potent TGF‐β‐activated kinase‐1 (TAK1) inhibitor LL‐Z1640‐2 (LLZ) on joint inflammation and bone destruction in collagen‐induced arthritis (CIA). Methods: LL‐Z1640‐2 was administered every other day in CIA mice. Clinical and histological evaluation was performed. Priming and activation of NLRP3 inflammasome and osteoclastogenic activity were assessed. Results: NLRP3 inflammasome formation was observed in synovial macrophages and osteoclasts (OCs) in CIA mice. TACE and RANKL were also overexpressed in synovial macrophages and fibroblasts, respectively, in the CIA joints. Treatment with LLZ mitigated all the above changes. As a result, LLZ markedly suppressed synovial hypertrophy and pannus formation to alleviate pain and inflammation in CIA mice. LLZ could block the priming and activation of NLRP3 inflammasome in RAW264.7 macrophage cell line, primary bone marrow macrophages and OCs upon treatment with LPS followed by ATP, thereby suppressing their IL‐1β production. LLZ also suppressed LPS‐induced production of TACE and TNF‐α in bone marrow macrophages and abolished IL‐1β‐induced production of MMP‐3, IL‐6 and RANKL in synovial fibroblasts. In addition, LLZ directly inhibits RANKL‐mediated OC formation and activation. Conclusion: TAK1 inhibition with LLZ may become a novel treatment strategy to effectively alleviate inflammasome‐mediated inflammation and RANKL‐induced osteoclastic bone destruction in joints alongside its potent suppression of TNF‐α and IL‐6 production and proteinase‐mediated pathological processes in RA. Abstract : In this study, we found that TGF‐β activated kinase‐1 (TAK1) mediates NLRP3 inflammasome‐induced inflammation and RANKL‐induced osteoclastic bone destruction alongside of TNF‐α and IL‐6 production and proteinase‐induced pathological processes in rheumatoid arthritis. The TAK1 inhibitor LL‐Z1640‐2 effectively alleviates joint inflammation and bone destruction in collagen‐induced arthritis.